2017
DOI: 10.1161/hypertensionaha.117.09536
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Adenosine Induces Placental DNA Hypomethylation Independent of A2B Receptor Signaling in Preeclampsia

Abstract: Consistent with this, detailed analysis of DNA from preeclampsia placentas showed that hypomethylation at specific promoter regions was associated with increased expression of specific genes that may contribute to the pathophysiology of Abstract-Preeclampsia is a prevalent pregnancy hypertensive disease with both maternal and fetal morbidity and mortality.Emerging evidence indicates that global placental DNA hypomethylation is observed in patients with preeclampsia and is linked to altered gene expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Roles of intracellular adenosine under the physiologic and pathologic conditions remain largely unknown. Recently, Huang et al reported that accumulated intracellular adenosine causes global placental DNA hypomethylation that is associated with PE . Aberrant gene expression in the placenta, due to the epigenetic modulation caused by the changes in DNA methylation status, is widely considered to be involved in the PE pathophysiology .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roles of intracellular adenosine under the physiologic and pathologic conditions remain largely unknown. Recently, Huang et al reported that accumulated intracellular adenosine causes global placental DNA hypomethylation that is associated with PE . Aberrant gene expression in the placenta, due to the epigenetic modulation caused by the changes in DNA methylation status, is widely considered to be involved in the PE pathophysiology .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Huang et al reported that accumulated intracellular adenosine causes global placental DNA hypomethylation that is associated with PE. 32 Aberrant gene expression in the placenta, due to the epigenetic modulation caused by the changes in DNA methylation status, is widely considered to be involved in the PE pathophysiology. 33,34 Huang et al showed that placental DNA hypomethylation status related to PE can be induced independent of ADORA2B activation, through the uptake of adenosine into the cytoplasm by equilibrative nucleoside transporters (ENTs).…”
Section: Discussionmentioning
confidence: 99%
“…ADORA2B, encoding the Adenosine A2B receptor, was shown to play a role in placental development and possibly in the pathophysiology of hypoxia and preeclampsia (PE) in pregnant women (Acurio et al, 2014;Darashchonak et al, 2014;Jia et al, 2012), a pathology which has also been associated with air pollution exposure during pregnancy (M. Pedersen et al, 2014). In both mice and humans, it has been demonstrated that activation of ADORA2B signalling contributes to the pathogenesis of PE (Huang et al, 2017), to small foetuses, small placentas and foetal growth restriction (Iriyama et al, 2015). The molecular basis of the functional link and relationship between ADORA2B gene and placenta DNA methylation, and the involvement of the ADORA2B protein in PE and birth outcomes are questions to be addressed in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, persistently elevated adenosine can be detrimental and contribute to multiple disease conditions, such pulmonary fibrosis, chronic kidney disease, and preeclampsia. [31][32][33][34][35] Adenosine signals via 4 G protein-coupled receptors, ADORA1, ADORA2A, ADORA2B, and ADORA3, which are expressed in a variety of cell types. 36 Among the 4 adenosine receptors, ADORA2B has the lowest affinity for adenosine and is activated by substantial accumulation of extracellular adenosine.…”
Section: Excess Extracellular Adenosine Is Detrimental In Scd Via Adomentioning
confidence: 99%